THE ROLE OF PARENTS IN ENCOURAGING SELF-DIRECTED LEARNING IN PRESCHOOL CHILDREN (A COMPARATIVE STUDY BETWEEN TRADITIONAL FAMILIES AND MODERN FAMILIES) - Sandi Pratama; Abdillah S; Nur Faisah Atirah (JURNAL NALAR PENDIDIKAN, 2024)
This research explains the role of parents in implementing the concept of "Merdeka Belajar" for children who have not yet pursued education in Makassar City, focusing on comparing traditional families and modern families. This research analyzes how traditional and modern families support and facilitate preschool children to learn independently. The research method involved surveys, interviews and observations of families representing both groups. The results illustrate significant differences in the approaches and practices of parents from traditional families and modern families towards the concept of "Independent Learning." There is a difference in approach between traditional and modern families supporting independent learning for preschool-age children. Traditional families tend to use more conventional methods, such as reading stories, providing particular time for learning, and showing patience when children have not mastered the material. Meanwhile, modern families utilize more digital media in the learning process. However, traditional and modern families try to stimulate children's curiosity, show appreciation, and create an exciting learning environment. Both face challenges, such as easily bored children with difficulty concentrating. Another difference lies in integrating learning activities with daily activities, which traditional families tend to do, while modern families utilize technology more in the learning process. There are differences in how parents can play a role in encouraging learning independence in preschool children in Makassar city.